Conductive Keratoplasty for Presbyopia - Awan, Abdul Hamid (Pakistan Journal of Ophthalmology, 2018)
Purpose: To assess the safety and efficacy of conductive keratoplasty (CK) in the treatment of plano presbyopia. Material and Methods: Twenty plano presbyopic patients (14 women and 6 men) underwent CK in non dominant eye. Mean age was 48.5 year (range 45 to 52 years). The post-operative target refraction for these eyes were minus 1.250 D. Results: Pre-op near refraction was +1.85 D (range +1.50 D to +2.25 D and near vision was J8 to J12. One year after conductive keratoplasty on non-dominant eye, the mean uncorrected near vision was J1 (range J1 to J3). 90% (18) eyes achieved J1 and 100% (all 20 eyes) achieved J3 or better. Conclusion: Conductive keratoplasty for the treatment of presbyopia provided safe and effective results one year following the initial surgery.